2015
DOI: 10.1021/acs.est.5b03452
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects of Nanoceria on Seed Production of Common Bean (Phaseolus vulgaris): A Proteomic Analysis

Abstract: The rapidly growing literature on the response of edible plants to nanoceria has provided evidence of its uptake and bioaccumulation, which delineates a possible route of entry into the food chain. However, little is known about how the residing organic matter in soil may affect the bioavailability and resulting impacts of nanoceria on plants. Here, we examined the effect of nanoceria exposure (62.5–500 mg/kg) on kidney bean (Phaseolus vulgaris) productivity and seed quality as a function of soil organic matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 55 publications
3
59
0
Order By: Relevance
“…Previous studies showed that CeO 2 -NPs promoted down-regulation of proteins in kidney beans S1 seeds, and altered starch and protein contents in wheat seeds. 2,6 It is difficult to determine the cause of accelerated growth and grain formation observed in the present study; however, analysis of first generation wheat seeds appeared to have improved grain biomass and amino and fatty acid concentrations. 3 Such alterations in macromolecular contents could have triggered the enhanced growth and early onset of grain production/maturity in the offspring of plants whose parents were exposed to Ce-500 during the first generation.…”
Section: Agronomic and Yield Parametersmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous studies showed that CeO 2 -NPs promoted down-regulation of proteins in kidney beans S1 seeds, and altered starch and protein contents in wheat seeds. 2,6 It is difficult to determine the cause of accelerated growth and grain formation observed in the present study; however, analysis of first generation wheat seeds appeared to have improved grain biomass and amino and fatty acid concentrations. 3 Such alterations in macromolecular contents could have triggered the enhanced growth and early onset of grain production/maturity in the offspring of plants whose parents were exposed to Ce-500 during the first generation.…”
Section: Agronomic and Yield Parametersmentioning
confidence: 54%
“…1 This peculiar property of CeO 2 -NPs stimulates physiological and biochemical changes in seeds harvested from plants that have been exposed to CeO 2 -NPs. Studies have revealed that CeO 2 -NPs induced significant changes on the quality of S1 seeds in wheat (Triticum aestivum L.), 2,3 barley (Hordeum vulgare L.), 4,5 kidney beans (Phaseolus vulgaris), 6 and soybean (Glycine max L.). 7 Findings have invariably established alterations in nutrient profile, grain/embryo physiology, and macromolecular composition in seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of publications have begun to explore the interaction between NPs and plants (Rico et al, 2011;Deng et al, 2014;Ma et al, 2010;Priester et al, 2012;Majumdar et al, 2015;Musante and White, 2012), the knowledge of the implications of NPs on the nutritional value of crop fruit is still limited. Rico et al showed that nCeO 2 decreased some of the nutrients in rice grains, including Fe, S, prolamin, glutelin, lauric and valeric acids, and starch.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study (Zhao et al, 2014) also showed that ZnO NPs and CeO 2 NPs at certain doses induced sugar, starch, and protein content alterations in cucumber fruits. Majumdar et al (2015) reported that phaseolin and lectins in bean (Phaseolus vulgaris) seed, which are associated with nutrient storage and carbohydrate metabolism, were down-regulated in a dose dependent way due to exposure of the plants to nCeO 2 . However, those studies analyzed a limited number of target metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of cutting or putting into the soil nanoparticles penetrate and transported to various parts of the plant. Some nanoparticles remain in the extracellular matrix; others remain inside the cells [20,41]. Dosage and absorption of nanoparticles can vary.…”
Section: Abstract: Nanoparticles Cerium Dioxide Biotransformation mentioning
confidence: 99%